Optimal monetary policy in the presence of food price subsidies - Ginn, William; Pourroy, Marc (Economic Modelling, 2019)
Food price subsidies are a prevalent means by which fiscal authorities may counteract food price volatility in middle-income countries (MIC). We develop a DSGE model for a MIC that captures this key channel of a policy induced price smoothing mechanism that is different to, yet in parallel with, the classic Calvo price stickiness approach, which can have consequential effects for monetary policy. We then use the model to address how the joint fiscal and monetary policy responds to an increase in inflation driven by a food price shock can affect welfare. We show that, in the presence of credit constrained households and households with a significant share of food expenditures, a coordinated reaction of fiscal and monetary policies via subsidized price targeting can improve aggregate welfare. Subsidies smooth prices and consumption, especially for credit constrained households, which can consequently result in an interest rate reaction less intensely with subsidized price targeting compared with headline price targeting.
CRIS-Team WoS Importer:2019-10-11